The First Record of an Hourglass Toad (Leptophryne borbonica) in The Core Zone of Bromo Tengger Semeru National Park and Its Ecological Aspects - Hanifa, Berry Fakhry; Fadhilah, Muhamad Aslam; Devi, Sandra Rafika; Hasyim, Muhammad Asmuni; Septiadi, Luhur (Journal of Tropical Biodiversity and Biotechnology, 2024)
Leptophryne borbonica is an amphibian species known for its sensitivity to environmental changes. Within the expansive Bromo Tengger Semeru National Park (TNBTS), new occurrences of L. borbonica have been discovered for the second time in another region of TNBTS (core area in Ireng-Ireng Block, Lumajang). This research provides the newest finding of L. borbonica and insights into the habitat assessment and potential food preferences of L. borbonica within TNBTS. The methodology involved the examination of morphology and meristics in L. borbonica. Habitat assessment and potential food indicated stable values. However, continued vigilance is essential due to vulnerability to volcanic threats.